Diversifikasi Produk Perikanan Lokal Berkelanjutan Melalui Inovasi Teknologi Berbasis Energi Terbarukan di Kelurahan Sibatua - Amiruddin; Aminuddin; Wahyudi; Zulfiani; Iris Sumariyanto (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
This community service program aims to support the diversification of sustainable local fishery products through the application of renewable energy-based technological innovations in Kelurahan Sibatua. Using the Participatory Action Research (PAR) approach, this initiative actively involves the community in training, demonstration, and implementation of solar panel technology for fish cooling boxes and processing fishery products into various value-added products such as milkfish nuggets, fish balls, and crackers. The results indicate that the solar panel technology used in the cooling boxes effectively improves the quality and shelf life of fish catches while reducing operational costs that previously relied on fossil energy. Additionally, technical training and mentoring successfully enhanced the community’s skills in fish processing and the use of renewable energy technologies. Evaluation through pre-test and post-test assessments showed a significant improvement in participants' competencies, from basic understanding to the application of technology and sustainable fishery product production.